(untitled) (Advancements in Homeopathic Research, 2025)
Introduction: Functional gynecological disorders such as menstrual irregularities, hormonal imbalance, and unexplained infertility are increasingly prevalent due to lifestyle and environmental factors. Homeopathic formulations offer non-hormonal alternatives with minimal adverse effects. Hertone™, a homeopathic uterotonic developed by Schwabe India, is indicated for a range of female reproductive conditions. This study aimed to assess its clinical effectiveness and safety in real-world settings through a post marketing physician survey. Methods: A structured questionnaire using Google Forms was circulated among prescribing homeopathic physicians across India. The survey captured responses from 131 doctors on parameters including effectiveness, speed of action, adverse effects, recommendation likelihood, and prescription frequency. Data were analyzed using descriptive statistics. Results: Among the 131 doctors, 93.9% rated Hertone™ with a score of 4 or 5 for effectiveness, indicating high satisfaction with its clinical benefits. Regarding onset of action, 81.7% reported noticeable therapeutic effects within three days. Adverse effects were rare, with 95.4% reporting no undesirable outcomes. Furthermore, 90.8% of doctors affirmed recommending Hertone™, and 84.73% had prescribed it more than 25 times, highlighting its high acceptance in regular practice. Conclusion: The findings suggest that Hertone™ is a well-tolerated, non-hormonal homeopathic formulation with favorable clinical outcomes in managing functional and hormonal reproductive disorders. Its widespread recommendation and frequent prescriptions reinforce its relevance as a safe adjunct in women’s reproductive healthcare.